NATO 2.0 : Reboot or Delete? - Kashmeri, Sarwar A. (Book collections on Project MUSE., 2011)
That will allow North America and Europe to act militarily together, should that ever become necessary. It is time for NATO 2.0, a new version of NATO, to fit the realities of an ever more integrated Europe in the twenty-first century. --Book Jacket.